1998
DOI: 10.1046/j.1365-313x.1998.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Ser6 in the maize actin‐depolymerizing factor, ZmADF3, is phosphorylated by a calcium‐stimulated protein kinase and is essential for the control of functional activity

Abstract: SummaryMaize actin-depolymerizing factor, ZmADF, binds both Gand F-actin and enhances in vitro actin dynamics. Evidence from studies on vertebrate ADF/cofilin supports the view that this class of protein responds to intracellular and extracellular signals and causes actin reorganization. As a test to determine whether such signal-responsive pathways existed in plants, this study addressed the ability of maize ADF to be phosphorylated and the likely effects of such phosphorylation on its capacity to modulate ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
104
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 32 publications
5
104
1
Order By: Relevance
“…Thus, there is strong evidence supporting a regulatory role for the Ca 21 gradient through imposing spatial control on the site of cell expansion in these tip-growing systems. Indeed, the structures of the apical actin cytoskeleton and its regulatory proteins (villins, gelsolins, and actin-depolymerizing factors; Smertenko et al, 1998;Tominaga et al, 2000;Allwood et al, 2001;Ketelaar et al, 2003;Fan et al, 2004) are thought to be regulated by the tip-high Ca 21 (Yokota et al, 2005). Similarly, there is evidence that annexins (Blackbourn et al, 1992;Clark et al, 1992;Carroll et al, 1998), phosphoinositide metabolism (Preuss et al, 2006), and calmodulin and protein kinases (Moutinho et al, 1998;Yoon et al, 2006) also play roles in sustaining tip growth and are regulated via the cytosolic Ca 21 gradient.…”
mentioning
confidence: 99%
“…Thus, there is strong evidence supporting a regulatory role for the Ca 21 gradient through imposing spatial control on the site of cell expansion in these tip-growing systems. Indeed, the structures of the apical actin cytoskeleton and its regulatory proteins (villins, gelsolins, and actin-depolymerizing factors; Smertenko et al, 1998;Tominaga et al, 2000;Allwood et al, 2001;Ketelaar et al, 2003;Fan et al, 2004) are thought to be regulated by the tip-high Ca 21 (Yokota et al, 2005). Similarly, there is evidence that annexins (Blackbourn et al, 1992;Clark et al, 1992;Carroll et al, 1998), phosphoinositide metabolism (Preuss et al, 2006), and calmodulin and protein kinases (Moutinho et al, 1998;Yoon et al, 2006) also play roles in sustaining tip growth and are regulated via the cytosolic Ca 21 gradient.…”
mentioning
confidence: 99%
“…The activity of ADF proteins is also regulated by phosphorylation in plant [20]. It has been reported that CDPKs phosphorylate ADFs in plant [19,20]. In this study, we identify that 14-3-3  interacts with ADF1 in plant and functions in ADF1 phosphorylation regulation to modulate actin cytoskeleton reorganization.…”
Section: Discussionmentioning
confidence: 65%
“…In plant, actin interacting proteins (AIP) interact with ADF proteins and enhance their F-actin severing and depolymerizing activity [41][42][43]. The activity of ADF proteins is also regulated by phosphorylation in plant [20]. It has been reported that CDPKs phosphorylate ADFs in plant [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations